Actividades verbales para mejorar la expresión oral de los estudiantes de nivel secundario I.E.I.P.S.M. 60078 Yraida Rojas Regra, provincia Mariscal Ramón Castilla, distrito de Pebas 2024 - Vela Cervantes, Paulo Ricardo (2025)
The present investigation had as purpose to determine in what way the verbal activities influence in the improvement of the oral expression of the students of the secondary level of the I.E.I.P.S.M. N° 60078 Yraida Rojas Regra, province Mariscal Ramón Castilla, district Pebas, 2024. Opting for a quantitative approach study, basic type and non-experimental cross-sectional correlational design, the sample consisted of 57 students in the first year of secondary school for the survey conducted with two questionnaires for data collection. The findings show that 52.6% of the students obtained a good level in the verbal activities; likewise, 38.6% of the students obtained a good level in oral expression. Therefore, it is determined that the verbal activities significantly influence the improvement of the oral expression of the students of the secondary level of the I.E.I.P.S.M. N° 60078 Yraida Rojas Regra, province Mariscal Ramón Castilla, district Pebas, 2024, this is evidenced in its level of significance of 0,000 (<0,05); likewise, it has been found that the variables present a very high positive correlation (rho=0,992). Likewise, the pronunciation dimension shows a very high positive correlation and a significance of rho=0.920 and p=0.000; similarly, the elocution dimension shows a very high positive correlation and a significance of rho=0.915 and p=0.000; also, the narration dimension shows a high positive correlation and a significance of rho=0.870 and p=0.000; finally, the verbal fluency dimension shows a high positive correlation and a significance of rho=0.840 and p=0.000.